Nexus between economic growth and foreign private investment: Evidence from Pakistan economy - Misbah Sadiq; Muhammad Usman; Aysha Zamir; Malik Shahzad Shabbir; Ankasha Arif (Cogent Economics & Finance, 2021)
This study examines the impact of economic growth along with taxes, technology, trade openness and exchange rate on the sustainability of foreign private investment (FPI) in Pakistan. This study uses random effects and generalized least squares estimators and contains data set starting from 1996 to 2017. The results indicate that the Pakistan economy has vastly positive influenced regarding the location and choice of emerging and developed countries' investment in the domestic market. Furthermore, emerging and developed economies investment increases the contribution among domestic firms to the national economy. The results, which are consistent across models, indicate that Pakistan's economy is more likely to receive FPI from emerging and developed economies, but the relative intensity of local government efforts, regardless of economic size. Moreover, an increase in likelihood will generate FPI from developed countries.
Keywords: 330; developed and emerging economies; Economic growth; foreign private investment; generalized least squares